Highly Efficient Copper-Catalyzed Dehydrogenative Cross-Coupling of Azoles with α-Amino Carbonyl Compounds - Ji, Jiu-Jian; Zhu, Zhi-Qiang; Xie, Zong-Bo; Tang, Juan; Yuan, En; Le, Zhang-Gao (Synthesis, 2021)
A novel and highly efficient dehydrogenative cross-coupling reaction between α-amino carbonyl compounds and azoles by copper catalysis using di-tert-butyl peroxide (DTBP) as an oxidant is described. A diverse range of azoles undergo the dehydrogenative imidoylation smoothly with various α-amino carbonyl compounds for the exclusive formation of the corresponding N-imidoyl azoles in high yields under air. The synthetic method has the advantages of good functional-group tolerance, wide substrate scope, excellent yields, and simple operation, thus providing a convenient and practical protocol for the synthesis of functionalized azoles.
Keywords: copper; dehydrogenation; imidoylation; azoles; α-amino ketones